Creative subtitling as film-transformative practice: From immersion to amazement in Edgar Pêra’s The Baron - Kapsaskis, Dionysios (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2024)
In this article, I examine creative subtitling as a cultural practice whose significance exceeds its use value as merely an enhanced variety of subtitling. The article’s main argument is that creative subtitling transforms the films that contain it by expanding further on their creative ideas, by foregrounding these films’ constructedness, and by embedding new layers of self-awareness in them. I begin the analysis by critiquing some recent studies on creative subtitling for downplaying the part of creativity in favour of a reductive conceptualisation of translation as meaning transfer. I then turn to Antoine Berman’s account of translation as reflexive practice, the ethical aim of which is to undo this conceptualisation and turn our attention away from meaning and closer to the experience of language itself. Taking translational creativity to mean literally this transformative “undoing,” in the last section, I examine the case of the creative subtitles of Edgar Pêra’s film, O barão [The Baron] (2011). I argue that these subtitles expand further on the creative ideas of this film while simultaneously “undoing” it: they take us out of a state of immersion in the story and into a state of “amazement” at the experience of the language of cinema itself.